Infection Studies in Pigs and Porcine Airway Epithelial Cells Reveal an Evolution of A(H1N1)pdm09 Influenza A Viruses Toward Lower Virulence. (18th February 2019) - Fu, Yuguang; Dürrwald, Ralf; Meng, Fandan; Tong, Jie; Wu, Nai-Huei; Su, Ang; Yin, Xiangping; Haas, Ludwig; Schmidtke, Michaela; Zell, Roland; Krumbholz, Andi; Herrler, Georg
Abstract : Investigations in pigs and porcine differentiated airway epithelial cells (PDAECs) reflect a loss in virulence of A(H1N1)pdm09 viruses isolated from humans and swine (2009–2015). PDAEC may be an in vitro test system for virulence of influenza A viruses. Abstract: We analyzed the virulence of pandemic H1N1 2009 influenza A viruses in vivo and in vitro. Selected viruses isolated in 2009, 2010, 2014, and 2015 were assessed using an aerosol-mediated high-dose infection model for pigs as well as air-liquid interface cultures of differentiated airway epithelial cells. Using a dyspnea score, rectal temperature, lung lesions, and viral load in the lung as parameters, the strains from 2014–2015 were significantly less virulent than the strains isolated in 2009–2010. In vitro, the viruses from 2009–2010 also differed from the 2014–2015 viruses by increased release of infectious virus, a more pronounced loss of ciliated cells, and a reduced thickness of the epithelial cell layer. Our in vivo and in vitro results reveal an evolution of A(H1N1)pdm09 viruses toward lower virulence. Our in vitro culture system can be used to predict the virulence of influenza viruses.